2005
DOI: 10.1111/j.1365-2443.2005.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2‐deficient mice are highly susceptible to cigarette smoke‐induced emphysema

Abstract: Inflammation, protease/anti-protease imbalance and oxidative stress play important roles in the pathogenesis of emphysema. Nrf2 counteracts oxidative tissue damage and inflammation through transcriptional activation via the anti-oxidant responsive element (ARE). To clarify the protective role of Nrf2 in the development of emphysema, the susceptibility of Nrf2-knockout mice to cigarette smoke (CS)-induced emphysema was examined. In Nrf2-knockout mice, emphysema was first observed at 8 weeks and exacerbated by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
226
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(245 citation statements)
references
References 44 publications
11
226
3
Order By: Relevance
“…Yoh et al (2001) reported that Nrf2-deficient female mice developed lupus-like autoimmune nephritis. It was also demonstrated that Nrf2-deficient mice exhibit prolonged inflammation during cutaneous wound healing and display enhanced bronchial inflammation and susceptibility to cigarette smoke-induced emphysema (Iizuka et al 2005). These data suggest that Nrf2 deficiency and the resulting impaired antioxidant activity are important in the determination of susceptibility to autoimmune and inflammatory diseases.…”
Section: Discussionmentioning
confidence: 88%
“…Yoh et al (2001) reported that Nrf2-deficient female mice developed lupus-like autoimmune nephritis. It was also demonstrated that Nrf2-deficient mice exhibit prolonged inflammation during cutaneous wound healing and display enhanced bronchial inflammation and susceptibility to cigarette smoke-induced emphysema (Iizuka et al 2005). These data suggest that Nrf2 deficiency and the resulting impaired antioxidant activity are important in the determination of susceptibility to autoimmune and inflammatory diseases.…”
Section: Discussionmentioning
confidence: 88%
“…NRF2-dependent gene expression is a central mediator in several pulmonary inflammatory diseases such as sepsis, asthma, and emphysema (Rangasamy et al, 2004(Rangasamy et al, , 2005Iizuka et al, 2005;Thimmulappa et al, 2006a). These studies are characterized by increased pulmonary inflammation in mice with a disruption of Nrf2 (Nrf2 −/− mice) compared with wild-type mice (Nrf2 +/+ mice), resulting in more severe pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to tobacco smoke increases inflammation, oxidative stress [1][2][3][4][5][6][7][8][9][10] and decreases antioxidant expression. [11][12][13][14][15] Direct and indirect studies have demonstrated that oxidative stress from reactive oxygen species (ROS) generated through mitochondria, xanthine oxidase, and the NADPH oxidase system [16][17][18][19][20][21] is one of the important factors in the pathogenesis of myocardial ischemia.…”
mentioning
confidence: 99%